PURA LINGSAR DALAM PENDEKATAN TEOLOGI HINDU - Sumertha, I Wayan (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2018)
Lingsar Temple, is a place of worship for two ethnicities and two religions namely Hindu Balinese ethnic, and Islam Wetu Telu ethnic Sasak. This phenomenon is something unique and unique in Lombok. Its uniqueness and uniqueness invite various audiences including academics to carry out various studies related to the values stored in it. Lingsar Temple as a symbol of monumental harmony of religious life in Lombok in particular and Indonesia in general. Likewise among tourists, both foreign and domestic, it is the main attraction as a leading tourist attraction for West Lombok regency in Lombok. Various values are contained in it, but the author is interested in researching the theological values that underlie Lingsar Temple. Based on a number of findings, it can be explained that the theology that underlies Lingsar Temple further emphasizes the worship of